The Incidence and Prevalence of Thromboangiitis Obliterans in Taiwan: A Nationwide, Population-based Analysis of Data Collected from 2002 to 2011 (Clinics, 2016)
OBJECTIVE: To estimate the incidence and prevalence of thromboangiitis obliterans in Taiwan in the period spanning from 2002 to 2011. METHODS: We identified all incident and prevalent cases with a diagnosis of thromboangiitis obliterans (International Classification of Diseases, Ninth Revision code 443.1) in the period spanning from 2002 to 2011 using Taiwan’s National Health Insurance Research Database. We calculated the age- and sex-specific incidence and prevalence rates of thromboangiitis obliterans during the study period. RESULTS: From 2002 to 2011, 158 patients were diagnosed with thromboangiitis obliterans; of these, 76% were men. Most (63%) of the patients were